Targeting Strategies for Renal Cell Carcinoma: From Renal Cancer Cells to Renal Cancer Stem Cells - Yuan, Zhi-xiang; Mo, Jingxin; Zhao, Guixian; Shu, Gang; Fu, Hua-lin; Zhao, Wei (Frontiers in Pharmacology, 2016)
Renal cell carcinoma (RCC) is a common form of urologic tumor that originates from the highly heterogeneous epithelium of renal tubules. Over the last decade, targeting therapies to renal cancer cells have transformed clinical care for RCC. Recently, it was proposed that renal cancer stem cells (CSCs) isolated from renal carcinomas were responsible for driving tumor growth and resistance to conventional chemotherapy and radiotherapy, according to the theory of CSCs; this has provided the rationale for therapies targeting this aggressive cell population. Precise identification of renal CSC populations and the complete cell hierarchy will accurately inform characterization of disease subtypes. This will ultimately contribute to more personalized and targeted therapies. Here, we summarize potential targeting strategies for renal cancer cells and renal CSCs, including tyrosine kinase inhibitors, mammalian target of rapamycin inhibitors (mTOR), interleukins, CSC marker inhibitors, bone morphogenetic protein-2, antibody drug conjugates, and nanomedicine. In conclusion, targeting therapies for RCC represent new directions for exploration and clinical investigation and they plant a seed of hope for advanced clinical care.